Murattal Al-Quran Therapy to Reduce Anxiety among Operating Patients - Lilis Lismayanti; Heri Ariyanto; Anisa Azmi; Annisa Fitria Nigusyanti; Rita Ayu Andira (Genius Journal, 2021)
Introduction: Surgery is a surgical procedure that opens or displays the part of the body to be treated and causes a psychological reaction, namely anxiety. This will cause delays in the operation that will be carried out. Anxiety is a psychological disorder that has excessive worry. Objective: The purpose of this literature review is to describe the effect of murratal Al-Qur'an therapy to reduce anxiety levels in surgery patients. Method: This study used a descriptive design with a literature review approach. The search for articles used six journal databases, namely PubMed, JSTOR, Wiley Online Library, Sage Journal, Taylor and Francis Online, Google Scholar. Selection is carried out by assessing articles that meet the inclusion criteria, including publication ranges for 2016-2020, in English and Indonesian as well as open access to full text pdf. While the exclusion criteria are book chapters, abstract proceeding, and posters Result: The results of the selection obtained seven articles with a total of 248 respondents. Based on the literature from the reviewed articles, it can be found that the interventions of Murattal Al-Quran therapy have an effect on reducing anxiety in surgery patients. Conclusion: Conclusion based on the literature review, it can be found that the provision of murattal alquran has a better activity in postoperative anxiety management. The suggestion of this literature review is that this murattal therapy can be applied directly in the hospital which aims to reduce anxiety level to post-patient patients.